A Selective Electrochemical Sensor for the Detection of Cd(II) Based on a Carbon Paste Electrode Impregnated with a Novel Ion-imprinted Hybrid Polymer - Adauto A. (2021)
An electrochemical sensor (CPE-IIHP) was developed for Cd(II) using a carbon paste electrode (CPE) impregnated with an ion-imprinted hybrid polymer (IIHP). A CPE-NIHP was also prepared for comparison. DPASV was used to optimize the sensor response and quantify Cd(II). The sensor presented a wide linear range from low concentrations of Cd(II): 1 to 100 ?g L?1 and high concentrations of Cd(II): 2.75 to 5.0 mg L?1. Ions such as Co(II), Pb(II), Ni(II), Zn(II), Fe(II), Fe(III), Sn(II) and Cu(II), showed no variation in the Cd(II) signal. The CPE-IIHP was successfully applied in river and drinking water analysis, revealing the great potential for its application.